Development of a vortex-assisted dispersive micro-solid-phase extraction using reduced graphene oxide/Fe3O4 nanocomposites for the determination of chlorfenson pesticide in green tea samples by high-performance liquid chromatography-ultraviolet detection - Aydin, Nazligul; Tekin, Zeynep; Turan, Nouha Bakaraki; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2023)
Pesticides are the group of chemicals used for the protection of plants against pests and other harmful organisms. The excessive and uncontrolled usage of pesticides may lead to the contamination of environment with pesticides posing a serious risk to human health and ecology. Based on this, the ability to detect and monitor the level of pesticides in different environmental compartments became a serious need. In this study, the reduced graphene oxide-magnetite nanocomposites (rGO-Fe3O4-NC)-based vortex-assisted dispersive micro-solid-phase extraction (VA-DMSPE) method was developed and optimized for the detection of chlorfenson pesticide by high-performance liquid chromatography-ultraviolet detection system. For this purpose, the synthesis of rGO-Fe3O4-NC was performed to be later applied as an adsorbent of the target analyte in the study. Furthermore, the extraction parameters such as the buffer pH, buffer amount, sorbent amount and eluent volume were optimized to obtain the highest detection efficiency of chlorfenson. The limit of detection (LOD) and limit of quantification (LOQ) were 0.02 and 0.07 mu g L-1, respectively. The improvement in the detection power was found to be 33.5. The proposed method accuracy was tested in green tea samples where the percent recovery for two different types of green tea samples was in the range of 96-109%.
Keywords: Chlorfenson; Dispersive micro-solid-phase extraction; Magnetite nanoparticles; Matrix matching; Green tea; WALLED CARBON NANOTUBES; HPLC; OXIDE; MICROEXTRACTION; ANTIBIOTICS; SEPARATION; RESIDUES; SORBENT; Chemistry